Perfil das crianças com transtorno do espectro autista atendidas no Centro de Atenção à Saúde da Mulher e da Criança da UFPA - PEREIRA, Alana Chelye de Lima (2023)
This study aims to profile children with Autistic Spectrum Disorder seen at the Center for Women and Children's Health Care from January 2019 to January 2020. This is a descriptive, cross-sectional study based on data from medical records. The investigation involved a population of 265 children. Collections were performed by analyzing the charts in medical records. The results show a higher frequency of males (79.2%) and coming from Belem (58.5%). The mean maternal age was 32 years, with an average of 14.5 years of schooling, and the main occupation was that of a housewife (58.5%). Referrals to CASMUC were made by pediatricians in 50.9% and from Primary Care in 35.9%, mostly due to language delays associated with behavioral problems (26%), and these referrals occurred on average at 59.8 months of age; the mothers were more frequently born until the second pregnancy (77.6%), by cesarean section (68.2%) and at term (87%), with birth weight above 2,500 grams (80.9%). Most mothers had prenatal care (98.9%), faced gestational complications (64.7%), and 67% had no neonatal complications, the latter being the most frequent type of isolated jaundice (37.9%). Regarding the care received, most have up-to-date vaccines (84.3%) and do not have adequate nutrition (80.9%), and mothers play a prominent role as the first observer of signs of ASD (52.3%), some use drugs (both licit and illicit), with a predominance of alcohol (43.2%). The socioeconomic conditions can be considered unsatisfactory because although the housing situations of most of the clientele are relatively adequate, most of the families are low-income (52.5%). We conclude then that there should be more care and investment in child health care, through the training of professionals at the primary care level, as well as the creation of new specialized centers in other locations for early detection of signs of ASD, as well as other developmental problems, since most referrals are made late, and many families need to migrate from distant cities in search of adequate care, thus requiring the decentralization of care.